GATING SYSTEMS FOR PRODUCTION OF HYDRODISTRIBUTORS - D. A. Volkov; A. D. Volkov (Литьë и металлургия)
Gating systems of the first group of special ways of casting into shell molds, casting in lined chill mold as more effective for production of hydrodistributors were developed and studied.